Pedestrian traffic is the main driver of macro- and large microplastic debris deposition in urban stormwater drains - Kozikowski, Nina; Corcoran, Patricia L. (Frontiers in Environmental Science, 2024)
Land-based sources are the greatest contributors of plastic pollution found in aquatic environments. Although plastic debris items spilling into natural watercourses from stormwater outflow sites have been investigated, this study provides details of the plastic items that can be trapped within stormwater drains prior to release. We examined macroplastic (>5 mm) and large microplastic (1–5 mm) debris that accumulated in LittaTrapTM devices at six drains over four seasonal periods in London, Ontario, Canada. Flotation, visual identification, microscopy and Fourier transform infrared spectroscopy (FTIR) were used to determine the drivers of plastic debris deposition. Macroplastics (MaPs) and microplastics (MPs) were identified in all 36 samples, and the totals ranged from 5–158 MaPs and 18–359 MPs per trap. Out of the 118 different MaPs found, the most common items were cigarette butts, wrappers, and expanded polystyrene. The main MPs were fragments, foams, and fibres. The most common macroplastic applications were “smoking”, “food/beverage packaging”, “household”, and non-food or beverage “packaging”. Microplastic particle compositions were mainly polyethylene and polypropylene, but other polymer types fall within the applications of construction (paints and resins), automotive/transportation, and electronics. The summer samples contained the greatest averages of plastic debris, and the drains located in busy pedestrian areas were associated with the highest debris counts. The results support pedestrian traffic as the main driver of plastic debris accumulation in urban London stormwater drains, which is controlled by seasonal weather conditions.